ANALISIS KESULITAN MATEMATIKA SISWA MA DALAM MENYELESAIKAN SOAL MENGGUNAKAN TAKSONOMI BLOOM - Muhammad Salimul Farhan; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
The purpose of this study is to show the types of difficulties MA students have in solving mathematical problems using the bloom taxonomy and the factors that cause it. The approach of this research is descriptive. As a sample of the study were 35 students of the X-MIA2 MA in Cimahi. Data collection is done by using a written test in the form of a description and equipped with interviews with the subject to track the type of difficulty; namely the difficulty of factual understanding, conceptual understanding, procedural understanding, and understanding of metacognitive and causal factors. The questions tested were 6 items. Data analysis was carried out by calculating many difficulties of students supported by the results of tests and interviews, then followed by conclusions. The results showed the highest metacognitive difficulties experienced by students. The order of the level of difficulty also occurs in terms of difficulties in knowing, understanding, applying, analyzing, evaluating, and creating. the factors that cause difficulties based on the results of a review of the answers of students who are not capable of mastering the concept, understanding the concept of determining a function of the function of the composition known, knowing in detail about the concept of function composition and carelessness of students in working on the problem, able to apply factors causes, understanding the material preconditions, determining strategies, the concept of the nature of the function of composition and algebraic operations, understanding the concept of the function of composition only knowing how to use it cannot use the strategy correctly and are also unable to find errors.